Semiologic aspects of epileptic seizures in 31 patients with hypothalamic hamartoma - Oehl, Bernhard; Brandt, Armin; Fauser, Susanne; Bast, Thomas; Trippel, Michael; Schulze-Bonhage, Andreas (Epilepsia, 2010)
Purpose: Characterization of seizure semiology in patients with hypothalamic hamartoma (HH) based on video-electroencephalography (EEG) monitoring (VEM). Methods: We retrospectively analyzed seizure semiology of 31 patients (20 male, mean age 23.5 years) who underwent VEM at the University Hospitals Freiburg or Heidelberg, Germany. Inclusion criteria were magnetic resonance evidence of an HH, no prior surgical or radiosurgical treatment, and at least two video-documented seizures. A total of 263 seizures were included (mean number of seizures/patient 8.5, range 2-10). To analyze age-dependent changes in seizure semiology, patients were grouped into “children” (3-11 years, n = 5), “adolescents” (12-17 years, n = 4), and “adults” (≥18 years, n = 22). Results: According to patient history, gelastic seizures had occurred in all patients, in 74% as the initial seizure type at epilepsy onset. In VEM, epileptic laughter varied from facial grinning to intense contractions of the diaphragm and body shaking. Unilateral motor signs were seen ipsi- and contralaterally to the HH. Tonic seizures were frequent and did not depend on the state of vigilance. Children, in contrast to adults and adolescents, did not show secondarily generalized tonic-clonic seizures, the gelastic component was the dominating and initial semiologic element, and seizures were significantly shorter. Conclusion: Seizure semiology is highly variable and age dependent. This may reflect network modulations with different propagation of ictal activity and/or secondary epileptogenesis. Detailed knowledge about such changes may contribute to both earlier recognition of seizures during childhood and better assignment of seizure types to a hypothalamic origin.
Gesehen am 12.06.2023